Unraveling the dynamics of loneliness in the Baltic-Nordic region: a comparative analysis in the wake of COVID-19 - Reine, Ieva; Miķelsone, Madara; Tomsone, Signe; Guðmundsson, Helgi; Ivanovs, Andrejs; Guðmundsson, Halldór S.; Koroļeva, Ilze (Frontiers in Public Health, 2024)
This study embarks on a comprehensive examination of loneliness among older adults in the Baltic-Nordic region, employing robust data and rigorous methodologies. Its goal is to unravel the nuances of loneliness within the varied cultural and socio-economic contexts of these regions, aiming to deepen our understanding of this complex issue. By identifying key factors such as demographics, social connections, and economic status, the research aspires to contribute significantly to the discourse on loneliness, paving the way for targeted public health interventions tailored to the older populations in these areas. Focusing on individuals aged 67 and above, the research harnesses data from the eighth wave of the Survey of Health, Ageing and Retirement in Europe (SHARE), conducted between June and August 2020. The demographic scrutiny encompasses 5,313 participants, divided between Nordic (Sweden, Denmark, Finland) and Baltic (Estonia, Latvia, Lithuania) countries. A separate analysis for Iceland, due to data constraints, relies on the HL20 study, enriching the regional comparative analysis. The findings reveal pronounced regional variations in loneliness, with the Baltic region showing fewer instances compared to the Nordic countries, which report the lowest levels. This disparity is attributed to the Nordic countries' robust social welfare systems and community involvement. Employment emerges as a significant factor in alleviating loneliness across the board, underscoring the value of social interaction and structured daily activities. Moreover, the study highlights the influence of gender and marital status on loneliness, with notable differences in the Baltic region and less pronounced in the Nordic countries. This suggests the impact of societal norms and cultural expectations on loneliness. The analysis also points to the role of education and health status in loneliness, indicating a multifaceted interplay of individual and societal factors. This research sheds light on the complexity of loneliness in the Baltic-Nordic context, offering insights for policy-making and intervention strategies.